CRITERIA AND STANDARDS FOR MEASURING AND EVALUATING MASTERY LEVELS - Arziqulov Abdixoliq Ulashevich (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In this article, the content of education, knowledge, skills and competences, control and measurement materials, criteria, norms, constructions and areas which are the basic of the measurement and th evaluation of the level of achievement , as well as pedagogical methods, aggregates, means of measurement, kinds and forms of control are explained.